Seed treatment with Trichoderma species for control of dampingoff of cowpea caused by Macrophomina phaseolina - Adekunle, A.T.; Cardwell, K.F.; Florini, D.A.; Ikotun, T. (Informa UK Limited, 2001)
Cowpea seeds treated with three Trichoderma spp. at four inoculum doses, and at four exposure times in three different formulations were planted in soils amended with Macrophomina phaseolin a, and assessed for stand establishment and post-emergence damping off. The highest percentage plant stands at 21 days after planting were 66% for T. koningii and T. harzianum , and 51% for Trichoderma sp., at 6.8 &#50 10 7 , 2.0 &#50 10 10 , and 1.0 &#50 10 7 colony forming units (CFUs) ml -1 , respectively. Across sampling dates and irrespective of time of exposure to the formulations, the T. harzianum and T. koningii formulations resulted in significantly greater percentage plant stands than the seeds treated with a Trichoderma sp. and the controls. Seed treatment formulations with Trichoderma spp. were derived from propagule suspensions at the most effective inoculum dose in Tween 80, in suspension with cooked cassava starch as an adhesive, or in a slurry with uncooked cassava starch. At 21 days, the suspensions with Tween 80 and cooked starch resulted in significantly higher percentage plant stands than the control, while stands from seeds treated in a slurry formulation and starch solutions were not different. Seed exposure to the different formulations for 10, 20, 30, or 40 min, provided mixed results. Seeds treated with benomyl at 0.5 g a.i/50 g resulted in 95 and 100% stands for the two sets of experiments, respectively.